THE COMPARISON OF DESCRIPTIVE TEXT WRITING ABILITY USING YOU TUBE DOWNLOADED VIDEO AND SERIAL PICTURES AT THE STUDENTS’OF SMPN 2 METROACADEMIC YEAR 2012/2013 - Eka Bayu Pramanca; Dedi Turmudi (Premise: Journal of English Education and Applied Linguistics, 2013)
This research discusses about how two different techniques affect the students’ ability in descriptive text at SMP N 2 Metro. The objectives of this research are (1) to know the difference result of using YouTube Downloaded Video and Serial Pictures media toward students’ writing ability in descriptive text and (2) to know which one is more effective of students’ writing ability in descriptive text instruction between learning by using YouTube Downloaded Video and Serial Pictures media. The implemented method is quantitative research design in that both researchers use true experimental research design. In this research , experimental and control class pre-test and post test are conducted. It is carried out at the first grade of SMP N 2 Metro in academic year 2012/2013. The population in this research is 7 different classes with total number of 224 students. 2 classes of the total population are taken as the samples; VII.1 students in experimental class and VII.2 students  in control class by using cluster random sampling technique.  The instruments of the research are tests, treatment and post-test. The data analyzing procedure uses t-test  and results the following output. The result of ttest is 3,96 and ttable  is 2,06. It means that tcount > ttable with the criterion of ttest is Ha is accepted if tcount  > ttable. So, there is any difference result of students’ writing ability using YouTube Downloaded Video and Serial Pictures Media. However; Youtube Downloaded Video media is more effective media than Serial Pictures media toward students’ writing ability. This research is consistent with the previous result of the studies and thus this technique is  recommended to use in writing instruction especially in descriptive text in order that students may feel fun and enjoy during the  learning process.